Una mirada al derecho en Europa y América Latina: caso litigio entre Colombia y Nicaragua; y España y Marruecos (2017)
"During the development of the ""Diplomado internacional sobre el derecho de la integración y los derechos humanos en Europa y América Latina"""", and the treatment given to the topics discussed, the consolidation of this work has sought to clarify several concepts which are immersed. Integration, as a fundamental concept to understand the functioning of the structure, economy, as the central axis of the countries for its capitalist field, and law, centered from the scope of rule, legal order, transformation of society and human rights . The rationale for this work will be structured as follows: How the European Union emerged as a unique economic and political association of its kind and composed of 28 European countries that together cover a large part of the continent, ends up being a producer in the higher legal order To the Member States themselves? In several cases, countries such as Colombia, Ecuador, Venezuela, despite having processes before the Commissions and Inter-American Court of Human Rights; And after knowing their failures and orders, these have been evaded by the countries, giving priority or that their State internally promulgate within its own norms and regulations. Contradiction that, it is interesting to deepen and analyze to conclude on whether the model is or is not successful for countries and continents. For our subject of study, we will have the analysis of the ligio on the sea of Colombia, Nicaragua, Spain and Morocco"